2021
DOI: 10.3389/fmicb.2021.623739
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Bacillus licheniformis Improves Intestinal Health of Subclinical Necrotic Enteritis-Challenged Broilers

Abstract: Necrotic enteritis infection poses a serious threat to poultry production, and there is an urgent need for searching effective antibiotic alternatives to control it with the global ban on in-feed antibiotics. This study was conducted to investigate the effects of dietary Bacillus licheniformis replacing enramycin on the growth performance and intestinal health of subclinical necrotic enteritis (SNE)-challenged broilers. In total, 504 1-day-old Arbor Acres male chickens were selected and subsequently assigned i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 102 publications
(140 reference statements)
1
41
0
Order By: Relevance
“…The expression of B mRNA and inflammatory factors further indicates that probiotic supply can effectively resist E. coli infection by enhancing the intestinal innate immune function of newborn calves. This is consistent with the results of previous studies (Dong et al, 2019;Boranbayeva et al, 2020;Kan et al, 2021). However, some studies believe that the physiological functions of different probiotic strains are different (Kang and Im, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The expression of B mRNA and inflammatory factors further indicates that probiotic supply can effectively resist E. coli infection by enhancing the intestinal innate immune function of newborn calves. This is consistent with the results of previous studies (Dong et al, 2019;Boranbayeva et al, 2020;Kan et al, 2021). However, some studies believe that the physiological functions of different probiotic strains are different (Kang and Im, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Overexpression of HSP90S impairs the function of T cells, leading to a decrease in IL-2 expression (Bae et al, 2013). Enteric pathogens that invade a host are recognized by pattern recognition receptors (Kan et al, 2021). Probiotic supplementation can promote toll like receptors (TLR) to recognize various pathogens and activate NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that the contents of total SCFAs and acetate were elevated in the multi-strain probiotic-treated group than in the control group, however, the contents of butyrate and propionate were not different from those in the control group. Kan et al ( 130 ) investigated the effects of Bacillus licheniformis on SCFAs content, and found that 3.2 × 10 9 CFU/kg Bacillus licheniformis resulted in a significant increase in formate in the cecum of broilers ( P = 0.027 ). In conclusion, the effects of probiotics on SCFAs production have been proven.…”
Section: Regulation Of Scfas Production In Intestinal Tract Of Poultrymentioning
confidence: 99%
“…The improvement of growth performance may be related to the beneficial metabolites produced by B. licheniformis, such as extracellular digestive enzymes, lysozymes, antifungal proteins, and various antibiotics (8,28). It is also possible that the addition of B. licheniformis can enhance the immunity of broilers by regulating the composition and metabolic function of intestinal microbiota (6,22,(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%